Penyuluhan manipulasi fotoperiod pada budidaya ikan patin (Pangasius hypopthalmus) di RW VIII Kelurahan Delima Kecamatan Tampan Pekanbaru - Windarti Windarti; Morina Riauwaty; Henni Syawal; Asmika H Simarmata; Isma Mulyani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
In the Delima Village, Pekanbaru City, there is a group of women that used to conduct a household scale fish culture activities. Most of them using a simple earthen pond. They did not apply any modern technique in culturing the fish. To improve the ability of the women community in culturing fish, a dissemination of environmental friendly fish culture technique was conducted. Slides and a simple manual book for conducting manipulated photoperiod in fish culture was used during the training. The community were also trained to construct tarp ponds, feeding, rearing Pangasius hypopthalmus and managing the water quality in the pond. Twenty five women that were belonged to “PKK” group attended the training. Before the training, their knowledge on fish culture was very low, but after the training, their knowledge improved by 85%. Results of monitoring and evaluation activities shown that the women from the PKK group were able to culture fish with manipulated photoperiod technique.